Factors Affecting University Brand Management in Vietnam: An Exploratory Study at Private Universities in Hanoi - Hue Minh Thi Hoang; Loc My Thi Nguyen; Kien Trung Nguyen; Truong Quang Dinh; Lua Thi Tran (Vietnam Journal of Education, 2023)
The research is aimed at identifying factors affecting university brand management by surveying private universities in Hanoi. Despite the vast amount of brand literature, it has received little attention in higher education settings, making the exploratory research method an appropriate choice. When observing the current situation from an unexplored perspective, the exploration design is a reasonable choice. Face-to-face and online interviews were conducted to exchange information and analyze the interaction of factors in brand management activities and the future university development orientation. Brand behavior and brand management of the university, competitiveness enhancement, and policies on university branding are among the factors that have a significant impact.